Structural blocks as flood control in Brazilian Pantanal - Ribeiro, Alisson André; Mioto, Camila Leonardo; Machado, Rômulo; Assine, Mario Luis [UNESP]; Guaraldo, Eliane; Filho, Antonio Conceição Paranhos (Universidade Federal do Rio de Janeiro, 2018)
The Pantanal basin formation and evolution are not well known and explained. This work brings new information showing the structural control over the physical environment of the Pantanal, one of the most important regions all around the world due to its biodiversity. We used different data sets from remote sensing data, the first set is a corrected SRTM (shuttle radar topographic mission) altimetric data and the second is a map of the major lineaments of Pantanal extracted from photointerpretation of satellite images. Both sets were confronted with the official borderlines of Pantanal and to other two limits defined by phytogeography and remote sensing images. It is possible to show that there is a good match between the internal limits of Pantanal and the interpreted lineaments. The altitudes decrease from N to S and from E to W and the slope analysis shows that this declivity is not homogeneous on these directions. The height difference between adjacent blocks is about 3 or 4 meters. Moreover, different regions have different mean altitudes and slope, although the slope inside each block is homogeneous. Considering Pantanal as a Cenozoic active basin, this paper proposes that the neotectonic controls these blocks and so the water flow in the basin, which in turn controls the fauna and flora of the region.
Blocos estruturais como controle da inundação no Pantanal Brasileiro
Keywords: DEM; Remote sensing; Sub-regions; Tectonics